AXIAL AND RADIAL EVALUATION OF THE BASIC DENSITY AND FIBER DIMENSIONS OF Guazuma crinita MARTIUS WOOD - Custodio, Manuel Chavesta; Tomazello-Filho, Mario; Carneiro, Mayara Elita Braz; Nisgoski, Silvana (Floresta, 2020)
The objective of the work was to evaluate the radial and longitudinal variation of the basic density and fiber dimensions of the Guazuma crinita Mart. Ten trees of five and eight years were used. They came from forest plantations of Maquizapallo located in the city of Puerto Inca, Huánuco – Peru. The variables analyzed were basic density based on the standard NTP 251.011: 2014, and the fibers characteristics. The trees were felled and sectioned into 4-meter logs, divided into three parts basal, middle and apical for density determination and fiber evaluations. In general, the basic density and the anatomical characteristics evaluated decrease from the base to the apex, meanwhile, they increase from the marrow to the cortex where age had a significant influence on the basic density but not on the anatomical characteristics, however, since the basic density is greater for 8 years, it could be used where no great effort is needed and also commercially.